SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA KARYAWAN MENGGUNAKAN METODE AHP DAN MAUT - Zulfikar Zulfikar; Umi Chotijah (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Employee performance is one of the main factors to determine whether the company is progressing or not. In an organization or agency can not be separated from the role of human resources, therefore assessment in performance is needed to measure the work of employees. Therefore the organization needs to conduct an assessment of each employee. Printing Company Subur Jaya in assessing employee performance still uses a subjective method with the assessment carried out directly by the company leader without any calculations. Decision Support System there is a solution for making decisions. There are many Decision Support System methods, but the researcher uses the AHP and MAUT methods to solve the problem. The AHP method is used for weighting each criterion and the MAUT method is used to generate alternative rankings. There are 30 alternative data used and 5 criteria such as: Performance, Honesty, Cooperation, Discipline, Age. The results obtained from this study are that the top 10 alternative data are stated to be good in performance and the bottom 10 data are declared to be poor with a test accuracy of 100%.